The Effect Of Job Satisfaction And Work Environment On Employee Performance Mediated By Work Motivation On Employees Of The Regional Secretariat Of Pandeglang Regency - Wohung, Antonius Barnabas Ala; Suparmoko, Muhammad; Wiguna, Wahyu (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to analyze the effect of job satisfaction and work environment on employee performance mediated by work motivation among civil servants at the Regional Secretariat of Pandeglang Regency. Employee performance in public institutions plays a crucial role in ensuring effective governance and quality public services. However, preliminary observations indicate that the performance of employees at the Regional Secretariat of Pandeglang remains suboptimal, as reflected in low attendance rates and inconsistent work discipline. This research employs a quantitative approach with survey methods using a structured questionnaire distributed to civil servants at the Regional Secretariat of Pandeglang. The population consists of 132 employees, with samples determined using appropriate sampling techniques. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to test both direct and indirect relationships among variables. The study investigates whether job satisfaction and work environment significantly influence employee performance, whether these variables affect work motivation, and whether work motivation mediates the relationship between job satisfaction, work environment, and employee performance. The findings are expected to contribute theoretically by enriching the field of human resource management, especially regarding motivation, job satisfaction, work environment, and employee performance in the public sector. Practically, the results provide recommendations for the Regional Secretariat of Pandeglang Regency to design strategic policies and programs to improve employee motivation and performance, thereby enhancing the effectiveness of governance and public service delivery.